Comprehensive Oral Exam - Arnold Rosenheck; Mahnaz Fatahzadeh (Association of American Medical Colleges, 2012)
Abstract Oral health is an integral component of total body health. Many systemic conditions have the potential to impact oral health and the latter can adversely compromise systemic health. A thorough physical examination also includes evaluation of the oral cavity and its associated structures, to screen for signs of local and systemic diseases. This module provides health practitioners with both a systematic method for evaluating the oral cavity and appropriate descriptive terminology in order to document and communicate their findings. It facilitates screening for oral abnormalities of local and systemic origin and promotes disease prevention and early detection. It also provides the foundation knowledge for additional oral health-related educational topics. This presentation has been used to teach medical students as part of a comprehensive oral health curriculum for several years. The student's participation and performance on departmental examinations and evaluations have been favorable, and further supports interprofessional collaborations between dental and medical educators.